Impact of main residential locations on depressive symptoms among older adults in China: A Blinder–Oaxaca decomposition analysis - Cheng, Yuqing; Yu, Qiutong; Li, Wei; Zuo, Genyong (Frontiers in Public Health, 2022)
Background: Following the development of urbanisation in China, the scale of internal migration and the number of immigrants among older adults are increasing. This requires us to pay attention to the living conditions and environment of internal migration. Many studies note a gap in the prevalence of depressive symptoms among older adults between different main residential locations. However, few studies have examined the extent to which main residential locations influence depressive symptoms among older adults. This study aims to quantify the effect of main residential locations on depressive symptoms. Methods: We followed the 2018 Chinese Longitudinal Health and Longevity Survey during which 8,210 individuals 65 years old and above were randomly selected from the community, to determine the effect of main residential locations on depressive symptoms among older adults. We further used the Blinder–Oaxaca decomposition method to quantify the explanatory factors of depressive symptom gaps among older adults and to estimate the relative effect of related individual characteristics on depressive symptoms. Results: We noted significant differences in depressive symptoms among older adults in different main residential locations. Rural-urban migrants had higher depressive symptoms scores (7.164). According to the Blinder-Oaxaca decomposition analysis, the high proportion of depressive symptom gap can be explained by years of education, income and exercise among different main residential locations groups. Additionally, in the main parts of the explained differences, the proportions of the limitation of activities of daily living (2.28%, 0.46%, and-52.11%) showed opposite effects, while their share in different main residential locations groups varied widely. Conclusion: Urbanisation has resulted in more rural people moving to urban areas in China; rural-urban migrants have the highest prevalence of depressive symptoms, which needs our attention. We need urgently integrate the health insurance and pension policy for urban and rural residents. This study provides a basis for formulating health policies and promoting the mental health of older adults in China as well as in low-and middle-income countries.